Pengaruh Pendekatan Teaching at the Right Level terhadap Kemampuan Problem Solving Siswa pada Materi Persamaan Linear di SMP Negeri 1 Kalasan - Nurmalitasari, Defri Aulia; Nugraha, Adhi Surya (Papanda, 2026)
The study aims to determine the implementation of the Teaching at the Right Level (TaRL) approach and whether there is a difference from the TaRL approach to students' problem-solving abilities in the One Variable Linear Equation material at SMP Negeri 1 Kalasan. This study used quantitative methods. The sample’ of this study were students of class VII B as an experimental class that received learning using the lecture method combined with the TaRL approach and VII D as a control class that used learning using the lecture method. The test instruments used were pretests and posttests that were adjusted to the problem-solving ability indicators in the form of essay questions. Data collection techniques using written tests and observations of learning activities. Data analysis techniques using descriptive statistics and t-tests. The results showed that the application of TaRL was divided into three levels of learning groups: two low-level groups, four medium-level groups, and two high-level groups. The results of the pretest and posttest were used to determine whether there was a difference between the average problem-solving ability scores of students who participated in learning using the lecture method with the TaRL approach and the lecture learning method. The results of statistical calculations using the t-test of two independent samples with the results of ???? − ℎ???????????????????? (2.3061) > ???? −???????????????????????? (1.67), then reject ????0 and accept ????1, meaning that there is a significant difference between the average problem solving ability scores of students who take part in learning using the lecture method and the TaRL approach to the lecture method.